Implementasi Work-Life Balance pada Guru Perempuan yang Telah Menikah - Neliwati, Neliwati; Ningsih, Euis Indah Kesuma; Purba Tambak, Sonia; Siregar, Ridho Khairul Azizi (EduInovasi: Journal of Basic Educational Studies, 2024)
This study aims to explain the implementation of work-life balance in married female teachers and to describe the factors that affect work-life balance in married female teachers. This study uses a qualitative method with a phenomenological approach. The subjects of this study are married female teachers who teach and hold positions in the madrasah organization at MAS PP Ad-Dhiya’ Meranti, with a total of three teachers, consisting of two senior teachers and one junior teacher with less than three years of work experience. Based on the data analysis and final findings of this study, the researcher has concluded that the work-life balance experienced by married female teachers at MAS PP Ad-Dhiya’ Meranti, where they acted as participants in this study, viewed from the WIPL dimension, married female teachers at MAS PP Ad-Dhiya’ Meranti are still not able to perfectly manage their personal and work lives. The personal lives of married female teachers at MAS PP Ad-Dhiya’ Meranti do not significantly disrupt their ability to work and have a career. The job as a teacher and holding an important position at work can improve the quality of their personal lives, both financially and in terms of personal life, married female teachers at MAS PP Ad-Dhiya’ Meranti can improve the quality of their work. The factors that affect the work-life balance of married female teachers are family support, especially from their husbands, and gratitude.